Experimental investigation of natural gas hydrate production characteristics via novel combination modes of depressurization with water flow erosion. (15th September 2019) - Chen, Bingbing; Sun, Huiru; Li, Kehan; Wang, Dayong; Yang, Mingjun
Highlights: A new combination mode of depressurization with water flow erosion is proposed. The phenomenon of MH existing after depressurization is observed by experiment. Water flow rate and decomposition pressure determine the MH decomposition rate. Heat transfer during depressurization is obvious changed by water flow erosion. The problem of ice generation is effectively mitigated by water flow erosion. Abstract: Depressurization is considered the most efficient method for natural gas hydrates (NGHs) exploitation. However, ice formation, hydrate reformation, and insufficient decomposition driving forces in the later stages of depressurization are the main issues to be solved. In this study, a more effective combination of depressurization with water flow erosion for the production of NGHs was investigated to promote efficient exploitation of methane hydrate (MH) by using in-situ magnetic resonance imaging. Three different MH decomposition modes were used, and water flow erosion was employed to eliminate the problem of incomplete MH decomposition in the later stages of depressurization, which is caused by insufficient driving forces and slower heat and mass transfer due to lower decomposition pressure and the protection effect of water films. The promotion of MH decomposition by water flow erosion was experimentally confirmed. Depressurization could decrease water-phase permeability in the sediment core and further optimize the water flow environment. Water flow erosion could greatly accelerate heat and mass transfer and provided extra driving force by increasing the chemical potential difference in the later stages of depressurization. In addition, the phenomenon of ice formation caused by sudden depressurization could be relieved by water flow erosion, which improved the ambient heat transfer, further changing the MH decomposition characteristics. The mutual promotion of MH decomposition by water flow erosion and depressurization was clearly demonstrated in this study.